THE INFLUENCE OF FINANCIAL LITERACY, OVERCONFIDENCE, RISK TOLERANCE, AND RISK PERCEPTION ON INVESTMENT DECISIONS IN THE CAPITAL MARKET - Indah Nur Kusuma Ningrum; Nur Hidayah; Naufal Afif (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2024)
An investment decision is a step taken to place capital in certain assets that generate profits in the future. This study aims to test and analyze financial literacy, overconfidence, risk tolerance, and risk perception that affect investment decisions in the capital market tested by generation Z in Magelang City. The data in this study were obtained from distributing questionnaires. The sampling technique in this study used purposive sampling consisting of 105 z generations in Magelang City. The analysis used is descriptive statistical test, the data quality test used is validity test and reliability test, model test and hypothesis test using multiple linear regression analysis The results showed that: (1) financial literacy and risk perception had a positive and significant effect on investment decisions, (2) overconfidence and risk tolerance had no effect on investment decisions by 37.3%, the remaining 62.7% were then explained by other factors outside the variables that had not been studied and were beyond the scope of this survey model